Training A Day with English - Dini Safitri; Chika Reza A; Tubagus Alfien B; Wenny Sabsela Marin; Ira Anjani; Nafila Tri Hutami (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2019)
Education is an activity that is common to every human being on this earth. Education cannot be separated from all forms of human activities. The teaching and learning process is certainly a core activity in the whole process of education in school or formal education. English is a language that is commonly used in several countries, therefore knowledge and learning of English is very important for the development of children's knowledge. Introduction, and learning things in the child's environment can initiate children's interest in learning English. This activity aims to provide knowledge to children about the use of English in everyday life, when children communicate in English, children become easier to know the meaning of words and their meanings because the material is learned based on the science of direct practice. Because the concentration of children at an early age is still very minimal and uncontrollable, the most appropriate method is by learning and playing where children can understand the material well because of the learning and teaching process that attracts children's interest. With this method, the interest of children is no longer only interested in how to play or just give rewards, but children will be happy with the repetition of the things he had learned before. So, children's interest in learning will increase with regard to things he already knows.